(untitled) (Sustainability in Debate, 2013)
The main goal of this paper is to contribute to the methodological improvement of the ecosystem services valuation process. The basic hypothesis adopted was that it should consider using the ecological-economic modeling as a basic tool required to better understand the ecological dynamics involved and incorporate other values of ecosystem services that otherwise would not be captured. As an important management tool, it is vital to go beyond with proposals for improving the ecosystem services valuation, in order to overcome its reductionist bias. In this sense the most important contribution of this paper is the proposal of a ecological-economic valuation approach, which is aimed at integrating the stricto sensu valuation to the more general analysis of changes in ecosystem services flows (ecosystem assessment) and its effects on economic variables.